Can isolated tibia intramedullary interlocking nailing in fracture distal 1/3rd both bone leg prevent fracture malalignment: will concurrent fibula fixation help? - Veluswamy, Vignesh; Loganathan, Senthil; Uma Shankar, Thiyagarajan; Jayaram Purushothaman, Pradeep; Dhanarajan, Gokul Raj (International Journal of Research in Orthopaedics, 2019)
Background: Different stand point prevails till date concerning fibular osteosynthesis in distal third both bone fracture fixation. This study was done to assess the post op alignment of distal third both bones fracture without fixing Fibula. Methods: A total of 30 patients who had distal 1/3rd extra articular tibia and fibula fractures were included in the study from July 2016 to April 2019. Tibial nailing was done in all cases with care is taken particularly to prevent malalingment of distal fragment. Radiological malalignment were assessed post operatively. Results: Of 30 patients, 5 patients had excellent results and 21 patients had good results, only 4 patients had fair results with valgus and varus malalignment, however these patients did not have any clinical problems associated with these malalignment at one year follow up. No patients had poor results. Valgus tibial malalignment is observed more frequently when fibular fracture is at proximal level. Conclusions: The level of Fibular fracture is important to determine when the fixation of this bone is indicated. Fixing ipsilateral tibial fracture with intramedullary interlocking (IMIL) nailing without fibular synthesis produce no gross change in alignment provided adequate care is taken for intra operative centering of the nail in both AP and lateral views.